A multilevel analysis of the cross-level interaction between drug use and a school-based culture of antisocial cognition as it relates to juvenile offending - Walters, Glenn D. (International journal of comparative and applied criminal justice, 2025)
The purpose of this study was to determine whether a cross-level interaction exists between an aggregate-level school-based culture of moral neutralisation and individual-level drug use in relation to concomitant criminal offending. A sample of 36,809 12-to-15-year-old youth (18,053 boys 18,717 girls, 39 sex unidentified) from the Second International Self-Reported Delinquency Study (ISRD2) served as participants in a multilevel analysis. Consistent with the research hypothesis, a culture of moral neutralisation, but not a pattern of school disorganisation, interacted with drug use to increase the likelihood of a youth’s concurrent involvement in criminal offending. These results suggest that a school culture built on the rationalisations, callous disregard, and low moral agency found in moral neutralisation will experience higher levels of criminal offending than a school culture low in these attributes, in part, because the school culture interacts with individual-level drug use.